Lecturer Performance Optimization: Uncovering the Secret of Productivity in the Academic World - Kartika, Ika; Widyastuti, Umi; Yohana, Corry; Sariwulan, Rd Tuty; Sunasa, Arman Aria (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
The focus of research in the context of this factor analysis is to identify and explore the dimensions that affect the work productivity of lecturers at Mercu Buana University Jakarta, Indonesia. This study aims to identify the main dimensions that affect the work productivity of lecturers at Mercu Buana University Jakarta. This research uses a quantitative approach with a descriptive type of research. The data collection technique used in this study was a questionnaire. The data analysis technique used in this study is Exploratory Factor Analysis (EFA), which has several critical steps. The results showed that crucial dimensions affect the work productivity of lecturers at Mercu Buana University Jakarta. Factor analysis shows a significant relationship between variables such as quality of work results, efficiency, effectiveness, and how lecturers work in the university environment. The relationship structure between these variables illustrates the essential components that play a role in understanding the work productivity of lecturers. These findings provide deeper insight into the factors that influence lecturer performance in the academic environment of Universitas Mercu Buana Jakarta.